Investigation on Exhaust Emission and Performance of SI-Matic Engine Applied Acetone-Butanol-Ethanol (ABE) Fuel Mixtures - Setyono, Gatot; Kholili, Navik; Kurniawan, Galih Ageng; Pratama, Deny Surya (Infotekmesin, 2024)
Acetone-butanol-ethanol (ABE) is a preferred alternative energy for SI engines. This research uses an experimental method with an automatic SI engine, RON-90 fuel mixed with ABE1 (12:8:1)v/v, ABE2 (15:10:1)v/v and ABE3 (1i8:12:1) v/v. Engine speed is 4000-10000rpm, and compression ratio is 11.6:1. Emission and engine performance testing used EPSG4-Gas analyzer and Dynotest-chassis type 50L-BRT. This research aims to explore the mixture of RON-90 and ABE to optimize performance and exhaust emissions. This research shows that torque increases by an average of 14.7% at an engine speed of 6000rpm. Power increased significantly with an average value of 9.5% at an engine speed of 8000rpm, MEP increased by 0.5%, and thermal efficiency increased by 7%. SFC experienced a fairly optimal decrease of 15.6% on average. The exhaust gas emissions produced are CO and HC. The reduction in CO and HC occurred in the ABE3 variant with values of 8.2% and 1.6%, respectively.